Lightntng protectton of quadruple circuit 275/132kV transmission line - Atailah, Mohd Nizam (2014)
This paper presents a comparative lightning performance study conducted on the 275kY and 132 kV transmission line from Kimanis and SPR Power Stations to PMU kolopis and PMU Lok Kawi, Sabah in quadruple circuit shielded transmission line using a software programs, TFlash. The line performance was investigated by using both a single stroke and a statistical performance analysis and considering cases of shielding failure and backflashover. A sensitivity analysis was carried out to determine the relationship between the flashover rate and the parameters influencing it. To improve the lightning performance of the line, transmission line surge arresters were introduced using different phase and line locations. Optimised arrester affangements are proposed